2018
DOI: 10.1001/jamainternmed.2018.2436
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Rates of Lower Extremity Amputation Among Patients With End-stage Renal Disease Who Receive Dialysis

Abstract: IMPORTANCE Patients with end-stage renal disease (ESRD) who receive dialysis are at high risk of lower extremity amputation. Recent studies indicate decreasing rates of lower extremity amputation in non-ESRD populations, but contemporary data for patients with ESRD who receive dialysis are lacking. OBJECTIVES To assess rates of lower extremity amputation among patients with ESRD who receive dialysis during a recent 15-year period; to analyze whether those rates differed by age, sex, diabetes, or geographic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 35 publications
2
37
0
2
Order By: Relevance
“…Studies included in this systematic review were very heterogeneous, as it was concluded in previous systematic reviews. Confounders and risk factors for LEAs and DFUs are well known in people with diabetes [70,71]. Few studies presented a strategy of risk classification in management (5/12) that allowed us to split the cohort according to the risk [38,41], but it was not possible for the other articles [54,59,60].…”
Section: Literature Comparison and Findingsmentioning
confidence: 99%
“…Studies included in this systematic review were very heterogeneous, as it was concluded in previous systematic reviews. Confounders and risk factors for LEAs and DFUs are well known in people with diabetes [70,71]. Few studies presented a strategy of risk classification in management (5/12) that allowed us to split the cohort according to the risk [38,41], but it was not possible for the other articles [54,59,60].…”
Section: Literature Comparison and Findingsmentioning
confidence: 99%
“…This increased risk of lower limb amputation was also observed in some observational studies and pharmacovigilance reports, yet whether it is a class effect or not remains an open question [113]. Of note, patients with ESRD who receive dialysis are at high risk of lower extremity amputation, which is associated with a high mortality rate, and among those people with ESRD, patients with diabetes had amputation rates more than five times as high as patients without diabetes [114].…”
Section: Sglt2 Inhibitorsmentioning
confidence: 72%
“…34,38 Recognized barriers to receipt of hospice care in this population include difficulty identifying those who are approaching the end of life, 28,39 limited patient and provider familiarity with palliative and hospice care, [40][41][42] and restrictions on Medicare coverage for concurrent hospice and dialysis services. 36,37,43 It is striking that despite widespread recognition that the presence of peripheral arterial disease and receipt of lower extremity amputation portend an exceedingly poor prognosis in this population, [3][4][5][6][7][8]19,44 Medicare beneficiaries with ESRD who undergo a lower extremity amputation near the end of their life receive more-not less-intensive patterns of care than other patients with ESRD. The significant amount of time that these patients spend in acute and subacute care settings during the last year of life is especially concerning because prior studies show that quality of end-of-life care for those who die in hospitals and nursing homes tends to be rated lower than for those who receive home hospice services.…”
Section: Discussionmentioning
confidence: 99%